(3YbO GdLeGf aj WHGFY efGaY GdMjhGfs - (3YHO Gddg Hf LHQjd Hf HNJjThYs ((3YHO Gddg Hf CMeO Hf Ydi GdTGaYi GdTYQGhi s)
(3ChdgG (B:s
(3bO PcQJ ai gPG GdcJGH eG JaQb ai cJH GdMceGA ef efGaY GdMjhGf s
(3BNQgG (B:s
(3jfJaY ai LQGMGJ GdCYUGH EPG SMb HGdNd hMOg Je GdcJGH HMeO Gddg hYhfg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI JjehQ (B39) s
Keywords: (3GdcjejGA h GdWHjYjGJs